AFFIRMATIVE POLICIES AND JUVENILE LITERATURE: REFLECTIONS ON THE REPRESENTATIONS OF CHILDHOOD - Galvao Ribeiro Ferreira, Eliane Aparecida [UNESP] (Univ Fed Goias, Campus Catalao, 2015)
This text aims to reflect on the formation of the young reader in the context of affirmative policies. For this, we will present a comparative analysis of the books Meu pe da laranja lima (2013), written by the Brazilian author Jose Mauro de Vasconcelos, and Commander Hussi (2006), by the Capeverdian author Jorge Araujo (1959-) using theories from the Reception Aesthetics. To achieve this goal, we built the hypothesis that both books have an emancipatory potential for their readers through the representations of childhood, expanding their horizons of expectation. This paper justifies itself because these books present an appealing structure that explores tenderness, pain, and allegorical elements in the representation of the imaginary its protagonists.
Keywords: Affirmative policies; Reception Aesthetics; reader formation